2014
DOI: 10.1517/14740338.2014.950653
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk associated with testosterone-boosting medications: a systematic review and meta-analysis

Abstract: The present systematic review and meta-analysis does not support a causal role between TS and adverse CV events. Our results are in agreement with a large body of literature from the last 20 years supporting TS of hypogonadal men as a valuable strategy in improving a patient's metabolic profile, reducing body fat and increasing lean muscle mass, which would ultimately reduce the risk of heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(191 citation statements)
references
References 135 publications
5
174
1
11
Order By: Relevance
“…The results of several large meta-analyses have generally not supported a causal role between testosterone treatment and cardiovascular events. [21][22][23][24] These metaanalyses are limited by the quality of the included studies, the heterogeneity of the testosterone levels in the populations assessed, and the use of different doses and routes of administration of testosterone replacement products.…”
Section: Treatmentmentioning
confidence: 99%
“…The results of several large meta-analyses have generally not supported a causal role between testosterone treatment and cardiovascular events. [21][22][23][24] These metaanalyses are limited by the quality of the included studies, the heterogeneity of the testosterone levels in the populations assessed, and the use of different doses and routes of administration of testosterone replacement products.…”
Section: Treatmentmentioning
confidence: 99%
“…Results of a recent metaanalysis (Xu et al 2013) that included the Testosterone in Older Men (TOM) trial (Basaria et al 2010) indicated that exogenous testosterone increased the risk of cardiovascularrelated events. However, the results of a more recent metaanalysis indicated that testosterone supplementation wasn't related to any increase in cardiovascular risk, supporting the hypothesis that there isn't a causal link between testosterone supplementation and adverse cardiovascular events (Corona et al 2014). Although much work has been reported recently in this field, the potential of testosterone replacement therapy to improve outcomes is still an uncertain matter.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported an excess of cardiovascular events in older men without pathological hypogonadism,6 but subsequent meta-analyses of randomised placebo controlled trials of adverse cardiovascular effects from testosterone treatment have provided discrepant interpretations 78 9 10 11 12 However, the overall risk ratios were 1.0 or greater in each trial, suggesting that these relatively short term analyses with wide confidence intervals were still too under-powered to be decisive 13. On the basis of congruent considerations, in June 2014 the US Food and Drug Administration and Health Canada required a new general label warning in the product information of all approved testosterone products about risk of venous thromboembolism after testosterone treatment 14…”
Section: Introductionmentioning
confidence: 99%